1987
DOI: 10.1111/j.1574-6968.1987.tb02247.x
|View full text |Cite
|
Sign up to set email alerts
|

Killer character inKluyveromycesyeasts: Activity onKloeckera apiculata

Abstract: The screening for ‘killer’ character among 23 strains of the genus Kluyveromyces showed the presence of three ‘killer’ strains (K. phaffii; K. vanudenii and K. wikenii). Their ‘killer’ activity against yeasts of other genera is in agreement with the results of others studies. Particularly K. phaffii inhibited many strains of Kloeckera apiculata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Previous studies have reported a broad spectrum of activity for Kpkt, and demonstrated its stability under winemaking conditions, indicating its promising features for use as a novel antiseptic agent in the wine and beverage industries [10,18,27]. In the present study, the mode of action Kpkt was characterized in view of its potential application as a natural antimicrobial agent.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have reported a broad spectrum of activity for Kpkt, and demonstrated its stability under winemaking conditions, indicating its promising features for use as a novel antiseptic agent in the wine and beverage industries [10,18,27]. In the present study, the mode of action Kpkt was characterized in view of its potential application as a natural antimicrobial agent.…”
Section: Discussionmentioning
confidence: 79%
“…Somewhat later, other researchers reported the antagonistic action of yeasts against other yeasts, involving the production of secondary metabolites known as killer toxins or “mycocins” (Young and Yagiu, 1978; Rosini and Cantini, 1987; Walker et al, 1995; Suzuki et al, 2001; Marquina et al, 2002). In summarizing the antimicrobial effects of yeasts present in fermented foods and beverages, Viljoen (2006) mentions actions of organic acids, antibiotic factors, volatile acids, hydrogen peroxide, and various other substrates excreted in the product.…”
Section: Introductionmentioning
confidence: 99%
“…K . wickerhamii CCY 21-41-1 is the same strain as that used by ROSINI and CANTINI [17] named K . wickenii U.C.D.…”
Section: Resultsmentioning
confidence: 99%